THE PRINCIPLE’S RULE OF NO PAR VALUE SHARES OF TRADING IN STOCK - Nur Sayidah; Ida Keriahenta Silalahi (Jurnal Dinamika Hukum, 2015)
Regulation of no par value shares in Indonesia is necessary because the stock market can not apply article 31 paragraph (2) of the Company Law number 40, 2007 because there is no further adjustment. This condition are known with the legal vacuum. The purpose of this article is to find the model of no par value shares regulation in Indonesia Capital Market. Further regulation of no par value shares is needed to fulfill this legal vacuum.  Research method in this artikel is using normative approach.  The results show that regulation of no par value share must fulfill four principles. There are (a) the principle of workable (b) the principle of global nature (compatible for domestic exchange rules  and the world exchange rules), (c) the principle of legal certainty in justice (d) the principle of legal protection. Keywords: capital market, regulation, principle.